Aspects of Metacognitive Awareness and Scientific Attitudes Toward Students' Higher-Level Thinking Skills - Stivani, Elly (Gunung Djati Conference Series, 2025)
The purpose of this study is to: Determine the magnitude of the contribution of the metacognitive awareness component to the component of high-order thinking ability of class X students about biodiversity at SMA N 1 Batang Kuis. Determine the magnitude of the contribution of the scientific attitude component to the component of high-order thinking ability of class X students about biodiversity at SMA N 1 Batang Kuis. This research is a type of quantitative descriptive approach research, which studies the magnitude of the contribution of aspects of metacognitive awareness and scientific attitudes to the high-order thinking skills of class X students. The results of this research are: The aspects of metacognitive awareness components that contribute most to the high-order thinking skills of class X students about biodiversity in SMA Negeri 1 Batang Kuis are evaluation (X1.8), improvement strategies (X1.7), planning (X1.4), monitoring comprehension (X1.6) and declarative knowledge (X1.1) with a contribution of 69.8%. The aspects of scientific attitude components that contribute most to the high-order thinking skills of class X students about biodiversity in SMA Negeri 1 Batang Kuis are the aspects of interest in increasing time to study science (X2.6) and career interest in science (X2.7) with a contribution of 62.5%.